Resection depth and layer of underwater versus conventional endoscopic mucosal resection of intermediate-sized colorectal polyps: A pilot study - Nomura, Hiroki; Tsuji, Shigetsugu; Utsunomiya, Manami; Kawasaki, Azusa; Tsuji, Kunihiro; Yoshida, Naohiro; Takemura, Kenichi; Katayanagi, Kazuyoshi; Minato, Hiroshi; Doyama, Hisashi (Endoscopy International Open, 2022)
Background and study aims Curability of colorectal tumors is associated with resection depth and layer in endoscopic resection. Underwater endoscopic mucosal resection (UEMR) has not undergone sufficient histopathological evaluation. We conducted a pilot study to compare the effectiveness, including resection depth and layer, of UEMR and conventional endoscopic mucosal resection (CEMR).Patients and methods This study was a single-center, retrospective study. Patients with colorectal lesions were treated by UEMR or CEMR between January 2018 and March 2020. Eligible patients were selected from included patients in a 1:1 ratio using propensity score matching. We compared the resection depth and layer and treatment results between the UEMR and CEMR groups.Results We evaluated 55 patients undergoing UEMR and 291 patients undergoing CEMR. Using propensity score matching, we analyzed 54 lesions in each group. The proportion of specimens containing submucosal tissue was 100 % in both groups. The median thickness of the submucosal tissue was significantly greater in the CEMR group than in the UEMR group [1235 µm (95 % confidence interval [CI], 1020–1530 µm) vs. 950 µm (95 % CI, 830–1090 µm), respectively]. However, vertical margins were negative in all lesions in both groups.Conclusions Our findings suggest that the median thickness of submucosal tissue in the UEMR group was about 1,000 μm. Even though the resection depth achieved with UEMR was more superficial than that achieved with CEMR, UEMR may be a treatment option, especially for colorectal lesions ≤ 20 mm in diameter without suspicious findings of submucosal deeply invasive cancer.